First‐Time Investigations on Cavitation in Rubber Parts Subjected to Constrained Tension Using In Situ Synchrotron X‐Ray Microtomography (SRμCT). Issue 11 (19th March 2021) - Euchler, Eric; Bernhardt, Ricardo; Wilde, Fabian; Schneider, Konrad; Heinrich, Gert; Tada, Toshio; Wießner, Sven; Stommel, Markus
Abstract : Cavitation under constrained tension is a critical failure phenomenon in rubber parts. For laboratory tests, strain constraints can be generated using disk‐shaped rubber samples, that is, pancake specimens. Due to suppressed transverse contractibility, the dominating hydrostatic tensile stress, which is the highest in the center part of a pancake specimen, causes an internal failure process controlled by the formation and growth of cavities. Laboratory X‐ray microtomography (μCT) is a powerful tool to monitor the evolution of a cavity population considering various aspects of geometrical as well as microstructural constraints. In the case of carbon black–reinforced styrene‐butadiene rubber, microscopic cavities are surrounded by a region of significantly lower material density. Due to detection limits, this region cannot be analyzed in depth with μCT. In this study, synchrotron X‐ray microtomography (SRμCT) in combination with a modular load frame is used, for the first time, to investigate the damaging phenomenon of cavitation in rubbers. Due to the high phase contrast that can be achieved only by SRμCT, the microstructure of regions of lower material density can be analyzed and, as a result, tiny satellite cavities are identified in the walls of neighboring microscopic cavities. Abstract : Herein, the image shows a microtomography (μCT) slice of a stretched and thus damaged rubber sample obtained by in situ synchrotron experiments. For the first time, tiny satellite defects next to major ones are monitored due to the high phase contrast of synchrotron μCT. As a result, low‐density regions observed via laboratory μCT can be explained.